2008
DOI: 10.1017/s1368980007001279
|View full text |Cite
|
Sign up to set email alerts
|

Whole-grain intake as a marker of healthy body weight and adiposity

Abstract: Objective: To review evidence relating to the consumption of whole grains and healthy body weight (BW). Design: Systematic review and analysis of observational studies reporting wholegrain consumption and measures of BW and adiposity, including the effect on macronutrient intakes and lifestyle factors. Setting: Medline and other databases were searched for the period 1990 to 2006 to produce a full reference list; observational studies were retained for further analysis if they included an appropriate control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 38 publications
5
71
0
2
Order By: Relevance
“…There is growing evidence to indicate dietary fibre and other NDC may have a role in BW regulation, with a number of studies suggesting the intake of dietary fibre and/or wholegrains are inversely associated with BW and/or BMI (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) . Dietary fibre and other NDC may therefore potentially have a role in the prevention and treatment of obesity.…”
Section: Colonic Delivery Of Scfa To Investigate Appetite Effects Fomentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence to indicate dietary fibre and other NDC may have a role in BW regulation, with a number of studies suggesting the intake of dietary fibre and/or wholegrains are inversely associated with BW and/or BMI (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) . Dietary fibre and other NDC may therefore potentially have a role in the prevention and treatment of obesity.…”
Section: Colonic Delivery Of Scfa To Investigate Appetite Effects Fomentioning
confidence: 99%
“…The need for strategies to prevent the rise in obesity is therefore becoming increasingly urgent. One strategy is to identify and develop foods that enhance satiety, thereby reducing subsequent energy intake (EI) (2,3) .SCFA have been suggested to have satiety-enhancing properties, with some researchers suggesting SCFA may explain the inverse association between dietary fibre intake and BW found in some observational studies (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) . This review considers the evidence for SCFA having a role in appetite regulation, starting first with the description of SCFA, followed by a discussion of the SCFA-activated receptors FFA receptor 2 (FFA2) and FFA receptor 3 (FFA3), which provide a rationale that SCFA may have a role in energy homeostasis.…”
mentioning
confidence: 99%
“…inflammation 45,46 insulin sensitivity, 45,47 and is inversely associated with weight gain and central adiposity. 48,49 Fruit and vegetable intake has been associated with lower blood pressure, 50,51 inflammation, 46,52 and risk of metabolic syndrome and central adiposity, 53,54 as well as a slower rate of weight gain. 49,55 Consumption of greater than five servings/day of fruits and vegetables is associated with the lowest risk of CVD relative to less than three servings/day.…”
Section: Introductionmentioning
confidence: 99%
“…Also, a recent European study found a positive association between white bread intake and an increase in waist circumference (Romaguera et al 2011). A review of 15 worldwide observational studies, including prospective ones (Koh-Banerjee et al 2004;Liu et al 2003), concluded that a high intake of whole grains (about 3 servings per day) is associated with a lower BMI and less central adiposity (Harland and Garton 2008), a conclusion borne out in central obesity studies of fiber (Du et al 2010), whole grain (McKeown et al 2010), and whole-grain bread (Bautista-Castano and Serra-Majem 2012). (Only a more recent British study of 1599 adults 19-64 years of age did not show an association between waist circumference and wholegrain intake (Thane et al 2009). )…”
Section: Discussionmentioning
confidence: 99%